Improving the Activity of Antimicrobial Peptides Against Aquatic Pathogen Bacteria by Amino Acid Substitutions and Changing the Ratio of Hydrophobic Residues - Tan, Rong; Wang, Meiru; Xu, Huiqin; Qin, Lu; Wang, Jun; Cui, Pengfei; Ru, Shaoguo (Frontiers in Microbiology, 2021)
With the increasing number of drug-resistant bacteria, there is an urgent need for new antimicrobial agents, and antimicrobial peptides, which exist in the human non-specific immune system, are one of the most promising candidates. It is an effective optimization strategy to modify antimicrobial peptides (AMPs) according to the distribution of amino acids and hydrophobic characteristics. The addition of bacterial pheromones to the N short peptide can increase the ability to recognize bacteria. In this study, we designed and synthesized AMP1-6 by amino acid substitution of mBjAMP1. Additionally, P-6, S-6, and L-6 were designed and synthesized by adding bacterial pheromones based on 1-6. Functional tests showed that the four AMPs had the ability to kill Gram-negative Vibrio anguillarum (V. anguillarum), Pseudomonas mendocina (P. mendocina), and Vibrio parahaemolyticus (V. parahaemolyticus), and Gram-positive Micrococcus luteus (M. luteus) and Listeria monocytogenes (L. monocytogenes). Additionally, all four AMPs induced permeabilization and depolarization of bacterial cell membranes and increased intracellular reactive oxygen species (ROS) levels. Importantly, they had little or no mammalian cytotoxicity. At the same time, 1-6 and L-6 protected the stability of intestinal flora in Sebastes schlegelii and increased the relative abundance of Lactobacillaceae. In summary, our results indicate that the designed AMPs have broad application prospects as a new type of polypeptide antimicrobial agent.